Pemanfaatan Daun Kelor untuk Gizi Seimbang pada Anak di Desa Mandalahaji Kecamatan Pacet Kabupaten Bandung Tahun 2025 - Maria Octavianti; Bekti Handayani; Marwati Marwati; Trijani Moedjiherwati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The 2021 Indonesian Nutritional Status Survey (SSGI) shows that 1 in 4 Indonesian children suffers from stunting and 1 in 10 children suffers from malnutrition. Good nutrition is a crucial foundation for optimal growth and development, especially for those growing up in vulnerable environments. According to the WHO, stunting is a failure of growth and development experienced by children due to prolonged inadequate nutritional intake, recurrent infectious diseases, and inadequate psychosocial stimulation. However, on the other hand, children who experience stunting are usually accompanied by developmental delays in various other organs, especially if malnutrition occurs during the first 1000 days of life (HPK). Stunting is defined as a child's length for age (PB/A) or height for age (H/A) that is lower than -2 standard deviations. Therefore, a child with stunting is definitely stunted, but a child who is stunted is not necessarily stunted. Stunting that occurs before a child is 2 years old is an indication of decreased cognitive abilities at a later age if not followed by adequate psychosocial stimulation, thus impacting academic or educational abilities later in life. Providing innovative education such as making moringa pudding is one way to present nutritious and creative food or drinks so that it can be accepted by kindergarten mothers who have toddlers and preschoolers. The content of moringa leaves is a food ingredient that has good nutritional value, especially for preventing stunting in children.